2020
DOI: 10.1186/s13031-020-00318-5
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between armed conflict and reproductive, maternal, newborn and child health and nutrition status and services in northeastern Nigeria: a mixed-methods case study

Abstract: Background Armed conflict between the militant Islamist group Boko Haram, other insurgents, and the Nigerian military has principally affected three states of northeastern Nigeria (Borno, Adamawa, Yobe) since 2002. An intensification of the conflict in 2009 brought the situation to increased international visibility. However, full-scale humanitarian intervention did not occur until 2016. Even prior to this period of armed conflict, reproductive, maternal, neonatal, and child health indicators were extremely lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…Additionally, changes to security, governance, health workforce, financing, supplies, and monitoring can affect the quality of maternal and child healthcare [ 37 ]. For example, interviews with government and UN officials working in conflict-affected Nigeria and Mali highlighted the difficulty in planning for healthcare resource allocation due to constant population movement, and in accessing remote populations in insecure settings [ 38 , 39 ], which explained poor maternal and child health indicators. Further empirical evidence from Nigeria has found that living in close proximity to development aid during conflict was associated with lower infant mortality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, changes to security, governance, health workforce, financing, supplies, and monitoring can affect the quality of maternal and child healthcare [ 37 ]. For example, interviews with government and UN officials working in conflict-affected Nigeria and Mali highlighted the difficulty in planning for healthcare resource allocation due to constant population movement, and in accessing remote populations in insecure settings [ 38 , 39 ], which explained poor maternal and child health indicators. Further empirical evidence from Nigeria has found that living in close proximity to development aid during conflict was associated with lower infant mortality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…By disrupting health infrastructure, mobility of health workers, and availability and accessibility of healthcare provisions, conflict exposure may negatively affect the utilization of care throughout the continuum. Also, conflict-led fear and security concerns, availability of transport facilities, wage loss, and injury or death of family members or neighbors also influence health-seeking behavior [ 14 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strong coordination that combines interventions and health system strengthening is essential for improving IDP health management ( Bile et al., 2011 , Olu et al., 2015 ). Involvement of various stakeholders in IDP healthcare, especially international organisations, offers several benefits ( Bile et al., 2011 , Olu et al., 2015 , Tyndall et al., 2020 , Low et al., 2014 ). For example, the health cluster partnerships approach in Uganda, also overseen by the MoH, improved the humanitarian response and health coordination ( Olu et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%